A word in your ear: What do podcasters' experiences tell us about creating podcasts for professional development? - Chris Morrison; Jane Secker; Mark Childs; Michael Collins (University of Huddersfield Press, 2023)
Podcasting by practitioners in Higher Education to support the development of peers is becoming more popular and yet, unlike its use in learning and assessment, remains little researched. This paper identifies some of the reasons that bring HE practitioners to podcast for professional development, some techniques and suggestions for making successful podcasts, and what the essential characteristics are of the medium that leads to podcasting being an effective tool for professional development. The discussion cites extensive quotes from interviews with creators of four podcasts aimed at HE practitioners, in order to give a rich account of the experiences of podcasting.